Asynchronous learning environment in english for civil engineering - Habil, Hadina; Md. Yusof, Masdinah Alauyah; Bunari, Ghazali; Ibrahim, Karni; Jan, Nurjannah (Faculty of Management and Human Resources Development, 2004)
This study proposed to examine learners’ experiences and perceptions in an asynchronous learning environment. The experiences and perceptions of the learners would assist the language teachers in understanding the impact of online discussion in language learning process. Questionnaires were distributed to the second year Civil Engineering students who were doing the UHB 2332 English for Civil Engineering subject. The study found that generally, the students were highly literate in using the Internet. They had positive experiences and perceptions in relation to asynchronous learning environment. Furthermore, the students have moderately positive views of the task of discussing online towards the use of asynchronous learning environment for language teaching and learning.